The Effect of Team Teaching Strategy to Learning Some Offensive Basketball Skills For Students - Abbas Abdulhamza Kadhem; Jaafar Ahmed Mahdi (CV Media Inti Teknologi, 2025)
This study aims to determine the effect of the team teaching strategy on learning several offensive basketball skills among students. A quantitative experimental method was used, involving a one-group pretest-posttest design. The sample consisted of 20 students selected through total sampling. The instruments used were tests of offensive basketball skills including passing, dribbling, and lay-up. Data analysis used the t-test to compare the pretest and posttest results. The findings showed a significant increase in students’ offensive basketball skills after the implementation of the team teaching strategy. The t-value (15.96) was higher than the t-table value (1.729) at a 5% significance level, indicating a statistically significant improvement. The average pretest score was 9.45, while the posttest average rose to 14.3. This suggests that the team teaching strategy positively influences students’ learning outcomes in basketball offensive skills. The implication of this research is that team teaching can be an effective instructional strategy to enhance technical performance in sports, especially in complex skill-based activities like basketball. In the future, this research may serve as a valuable reference for developing innovative teaching models and for further studies on collaborative instruction across different sports and educational levels.